2012
DOI: 10.1007/s00417-012-2219-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spectralis-OCT, GDxVCC and GDxECC in assessing retinal nerve fiber layer (RNFL) in glaucomatous patients

Abstract: RNFL thickness assessments between GDxVCC, GDxECC, and Spectralis-OCT cannot be directly compared. The assessments are generally higher with Spectralis-OCT than with GDxVCC and GDxECC, because of differences in method of the devices. The atypical retardation pattern has a major impact on the RNFL thickness results of GDx devices. This must be taken into account when evaluating the assessed RNFL thickness results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Recently, we were able to demonstrate that an undifferentiated comparison of RNFL thickness assessment between GDx VCC, GDx Pro and Spectralis OCT is not feasible. The measurements with SD OCTs are generally higher than with GDx VCC and GDx Pro, the reasons being physical differences of the imaging methods [ 8 ] but also software dependent. In the standard clinical glaucoma RNFL protocols and printouts of almost all OCT devices, blood vessels are not extracted from RNFL measurements [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we were able to demonstrate that an undifferentiated comparison of RNFL thickness assessment between GDx VCC, GDx Pro and Spectralis OCT is not feasible. The measurements with SD OCTs are generally higher than with GDx VCC and GDx Pro, the reasons being physical differences of the imaging methods [ 8 ] but also software dependent. In the standard clinical glaucoma RNFL protocols and printouts of almost all OCT devices, blood vessels are not extracted from RNFL measurements [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The atypical retardation pattern (ARP) has a major impact on the RNFL thickness results of GDx devices and it is significantly lower in GDx Pro than in GDx VCC. This must be taken into consideration when evaluting RNFL thickness measurements and may be an explanation for the higher correlations of GDx Pro with SD OCT data [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schallenberg et al . [ 75 ] used GDx-VCC, GDx-ECC, and Spectralis-OCT to study RNFL measurements in 92 eyes of 92 glaucoma patients with various amount of glaucomatous damage and found that they cannot be directly compared because of differences in method of the devices.…”
Section: Comparison With Other Diagnostic Modalitiesmentioning
confidence: 99%
“…The OCT device used in our study, Spectralis HRA+OCT, is the only device has a long wavelength of 870 nm allowing a better penetration through existing cataract. And together with other enhancement such as a coefficient variance of less than 1.0, a faster scanning speed of 40000 A scans/sec, better axial resolution of 7 um and an eye-tracking system to account for eye movement, this probably explain why the RNFL thickness measurements by Spectalis HRA+OCT is less susceptible to the effect of media opacity as compared to previous literature using other OCT devices [24,25].…”
Section: Effect Of Cataract Extraction On Rnfl Thickness Measured By Octmentioning
confidence: 89%